2014
DOI: 10.1038/ncomms6514
|View full text |Cite
|
Sign up to set email alerts
|

Pathological roles of the VEGF/SphK pathway in Niemann–Pick type C neurons

Abstract: Sphingosine is a major storage compound in Niemann–Pick type C disease (NP–C), although the pathological role(s) of this accumulation have not been fully characterized. Here we found that sphingosine kinase (SphK) activity is reduced in NP–C patient fibroblasts and NP–C mouse Purkinje neurons (PNs) due to defective vascular endothelial growth factor (VEGF) levels. Sphingosine accumulation due to inactivation of VEGF/SphK pathway led to PNs loss via inhibition of autophagosome–lysosome fusion in NP–C mice. VEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 45 publications
6
61
0
Order By: Relevance
“…Antibodies targeting phosphoproteins were incubated with 1 mM sodium orthovanadate in 0.5% BSA/TBS. The following primary antibodies were used: 1:2,000 Vps15 for mouse studies (Novus Biologicals NBP1-30463) 39 , 1:1,000 VPS15 for human studies (Abcam ab124817, Abcam ab128903) 41 , 1:500 Vps34 (Cell Signaling, #3811) 42,43 , 1:1,000 Beclin1 (Cell Signaling #3738) 44 , 1:500 p62 (Novus Biologicals, H00008878-M01) 45 , 1:2,000 GAPDH (Millipore, MAB3 74) 26,46 , 1:1,000 ubiquitin (Santa Cruz, sc-8017) 47 , 1:10,000 α-tubulin (Sigma Aldrich, T6199) 48 , 1:100 LC3 (Nanotools, 0260-100/LC3-2G6) 49 , 1:600 EGFR (Cell Signaling #4267 S) 50 , 1:200 Nischarin (Santa Cruz, sc-365364) 21 , 1:500 PAK1 T423 (Cell Signaling, #2601 S) 51 and 1:500 N -terminal Vps15 antibody (Proteintech, 17894-1-AP). Western blots were quantified using ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies targeting phosphoproteins were incubated with 1 mM sodium orthovanadate in 0.5% BSA/TBS. The following primary antibodies were used: 1:2,000 Vps15 for mouse studies (Novus Biologicals NBP1-30463) 39 , 1:1,000 VPS15 for human studies (Abcam ab124817, Abcam ab128903) 41 , 1:500 Vps34 (Cell Signaling, #3811) 42,43 , 1:1,000 Beclin1 (Cell Signaling #3738) 44 , 1:500 p62 (Novus Biologicals, H00008878-M01) 45 , 1:2,000 GAPDH (Millipore, MAB3 74) 26,46 , 1:1,000 ubiquitin (Santa Cruz, sc-8017) 47 , 1:10,000 α-tubulin (Sigma Aldrich, T6199) 48 , 1:100 LC3 (Nanotools, 0260-100/LC3-2G6) 49 , 1:600 EGFR (Cell Signaling #4267 S) 50 , 1:200 Nischarin (Santa Cruz, sc-365364) 21 , 1:500 PAK1 T423 (Cell Signaling, #2601 S) 51 and 1:500 N -terminal Vps15 antibody (Proteintech, 17894-1-AP). Western blots were quantified using ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to our phenotype, NP-C fibroblasts accumulate LEs enriched in sphingolipids and cholesterol (Sarkar et al, 2014). As SphK activity is suppressed in NP-C (Lee et al, 2014), we propose that a failure to recruit SphK to endosomal membranes may drive Sph accumulation during the pathogenesis of NP-C. Despite functional lysosomes, NP-C cells have impaired autophagic flux due to the failure to recruit autophagic SNARE machinery to LEs (Sarkar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Niemann-pick type C-neurological impairments of early onset NPC1 include cerebellar ataxia, strongly implicating the loss of Purkinje cells in the cerebellum [144]. Although, there have been no published reports yet exclusively on iPSC derived Purkinje neurons, a study by Lee et al [145], reported that iPSCs-derived neurons from NPC1 patients accumulated cholesterol and sphingosine, and had reduced levels of sphingosine kinase (SphK) activity and VEGF (vesicular endothelial growth factor) levels. The authors proposed that sphingosine accumulation was caused by inactivation of the VEGF/SphK activity, leading to inhibition of autophagosome-lysosome fusion.…”
Section: Ipscs As An Emerging Model To Study Human Neuronal Dysfunctimentioning
confidence: 99%